Alginate‐based coatings charged with hydroxyapatite and quercetin for fresh‐cut papaya shelf life. (6th June 2022) - Montone, Angela Michela Immacolata; Malvano, Francesca; Pham, Phuong Ly; Cinquanta, Luciano; Capparelli, Rosanna; Capuano, Federico; Albanese, Donatella
Summary: In this study, the effect of alginate‐based coatings charged with quercetin glycoside compounds and hydroxyapatite/quercetin glycoside compounds (HA/QUE) on the microbiological quality, and on bioactive compounds of fresh‐cut papaya, was evaluated for 14 days at 6 °C. Alginate coatings with hydroxyapatite/quercetin showed a high capability to slow down the growth of all microbiological parameters investigated. At the end of cold storage, the total bacteria count in papaya samples covered with HA/QUE alginate coating was 4.8 log CFU g −1 which is significantly lower ( P < 0.05) than 8.3 log CFU g −1 for uncoated samples. Total carotenoids' percentage decrease, at the end of storage, was about 20% in papaya with active coatings, with respect to the losses of 39 and 35%, registered in uncoated and alginate‐coated samples respectively. Vitamin C content and the antioxidant activity measured in papaya coated with HA/QUE alginate showed significantly higher values ( P < 0.05) for each storage day than those detected for control‐ and alginate‐coated samples. Based on the sensory evaluation, active‐coated fresh‐cut papaya reached, at the end of the storage period, suitable values for commercial purposes. Abstract : Figure. 1. Changes in O2 (%) (a) and CO2 (%) (b) in fresh‐cut papaya packages during the storage time at 6degC.